Exploring Language Teachers' Beliefs About the Medium of Instruction and Actual Practices Using Complex Dynamic System Theory - Gao, Yang; Zhou, Yafang (Frontiers in Education, 2021)
This paper explores the relations between teacher beliefs and practices about the medium of instruction from the perspective of complex dynamic systems theory. Through a functional framework of teacher classroom discourse, mixed analytical models were adopted to fully describe the close interaction and non-linear relations between teacher beliefs and practices. Data were collected through classroom observations and semi-structured interviews from three college teachers working in a typical research-based university in northeast China. The findings revealed the complex and dynamic relations between teacher beliefs and practices about the medium of instruction. The consistency and inconsistency between the analysis of interviews and classroom observations represented the tensions and changes between teacher beliefs and practices about the medium of instruction. The study calls for attention to the socially situated and co-evolving relations between teacher beliefs and practices and how they develop with contextual affordances, attractor states, flexible goals, and high dependence on initial conditions.